Tubularized Penile-Flap Urethroplasty Using a Fasciocutaneous Random Pedicled Flap for Recurrent Anterior Urethral Stricture - Lee, Yong Jig (The Korean Society of Plastic and Reconstructive Surgeons, 2012)
This report describes the use of a tubularized random flap for the curative treatment of recurrent anterior urethral stricture. Under the condition of pendulous lithotomy and suprapubic cystostomy, the urethral stricture was removed via a midline ventral penile incision followed by elevation of the flap and insertion of an 18-Fr catheter. Subcutaneous buried interrupted sutures were used to reapproximate the waterproof tubularized neourethra and to coapt with the neourethra and each stump of the urethra, first proximally and then distally. The defect of the penile shaft was covered by advancement of the surrounding scrotal flap. The indwelling catheter was maintained for 21 days. A 9 month postoperative cystoscopy showed no flap necrosis, no mechanical stricture, and no hair growth on the lumen of the neourethra. The patient showed no voiding discomfort 6 months after the operation. The advantages of this procedure are the lack of need for microsurgery, shortening of admission, the use of only spinal anesthesia (no general anesthesia), and a relatively short operative time. The tubularized unilateral penile fasciocutaneous flap should be considered an option for initial flap urethroplasty as a curative technique.